Teacher Professional Development in Light of the Saudi Vision 2030 and International Experiences - Altalhy, Afnan Fayiz Awad; Masoud, Afnan Omar; Homdi, Taghreed Abdu; Alqithami, Faridah Rashid; Alharbi, Nora Abdulaziz; Alamrani, Dalal Mutlaq; Alsaadi, Reem Khudher; Alutaybi, Maraam Misri (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying the reality of teacher professional development in the Kingdom of Saudi Arabia, Finland, Japan, South Korea, and Malaysia. The similarities and differences explored the compared countries to highlight how to benefit in developing Saudi teacher's professional development programs in the light of the Saudi Vision 2030. Comparisons were identified in the following fields: academic, subjective, human relations, scientific research, teaching performance, technology, teacher licensing, and in-service training forms. The study resulted in identifying the similarities and differences between the Kingdom of Saudi Arabia and the compared countries. The study provided several recommendations and proposals as establishing community partnerships with technical and vocational training institutions to raise the efficiency of digital skills among teachers and adopting a method of teacher exchange among schools to provide equal educational opportunities for students and teachers.
Keywords: Teacher professional development; Kingdom of Saudi Arabia; vision 2030; compared countries; comparative study